1999
DOI: 10.1046/j.1365-3156.1999.00489.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal responses to childhood fevers: a comparison of rural and urban residents in coastal Kenya

Abstract: SummaryUrbanization is an important demographic phenomenon in sub-Saharan Africa, and rural-urban migration remains a major contributor to urban growth. In a context of sustained economic recession, these demographic processes have been associated with a rise in urban poverty and ill health. Developments in health service provision need to reflect new needs arising from demographic and disease ecology change. In malariaendemic coastal Kenya, we compared lifelong rural (n ϭ 248) and urban resident (n ϭ 284) Mij… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 25 publications
2
99
0
Order By: Relevance
“…A systematic random sampling technique using an interval of every fourth house was then used to select the households. A household was defined as 'a person or group of people living in the same house, who are answerable to the same head and share a common source of food and/or income 4 . The starting point was determined by spinning a bottle within each village square and picking the first house that is closest to the mouth of the bottle.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic random sampling technique using an interval of every fourth house was then used to select the households. A household was defined as 'a person or group of people living in the same house, who are answerable to the same head and share a common source of food and/or income 4 . The starting point was determined by spinning a bottle within each village square and picking the first house that is closest to the mouth of the bottle.…”
Section: Methodsmentioning
confidence: 99%
“…In sub-Saharan Africa, rural and urban populations differ demographically, in socio-economic and cultural composition, and in proximity to formal and informal treatment souces 4 . Malaria is one of humanity's worst diseases and the suffering it causes is now a global crisis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has recently been reported that the preference for drug vendors in Nigeria, included the lack of functional health facilities, affordability of vendor's drugs and their closeness to the people (Idowu et al, 2006). Molyneux et al (1999) and Salako et al (2001) made similar conclusions. In this study appropriateness of treatment actions was based mainly on reported parental actions.…”
Section: Discussionmentioning
confidence: 88%
“…This was an important factor in the rural and urban samples' similarity in responses to child illnesses for example, despite relatively good physical access to formal and informal biomedical services in the urban study area: (28) over the year preceding the interviews, just over half of all rural and urban mothers had used bio cultural (or "traditional") therapy to treat a child, and approximately one-fifth of rural and urban mothers' actions in response to childhood convulsions involved consulting a healer (22 per cent (n= 9) and 19 per cent (n=24), respectively); over the two weeks preceding the interviews, 69 per cent of rural and urban mothers used shop-bought medicines first, or only, to treat uncomplicated childhood fevers.…”
Section: B Mobility and Intra-household Relationsmentioning
confidence: 99%